Mall Apps Effects On Students' Esl Writing Achievement, Attitudes Towards Learner Autonomy And Mobile Learning - Fayed, Ismail Abdelwahab Ragab (2017)
This study investigates the effect of mobile assisted language learning (MALL) apps on students’ ESL writing achievement and their attitudes towards learner autonomy (LA) and mobile learning in the Foundation Program at Qatar University. A web-based writing app was developed by the researcher with different weekly learning modules and activities to be delivered through students’ own smartphones. The app modules were developed based on both the constructivist and the self-determination (SDT) learning theories. Moreover, the ASSURE instructional design model was used in the app design using a “bring your own device” (BYOD) approach.